A new and accurate map of Scandinavia, or the northern crowns of Sweden, Denmark, and Norway: drawn from the most approv'd maps and charts, and adjusted by astronoml. observations - Bowen, Emanuel ([London]: [s.n.], [1747], 1747)
Teoksessa A complete system of geography / E. Bowen, (London) 1747. Plate n:o 25. 0-meridiaani: London: Koordinaattiasteikko: W15°-E55°, N75°-53°. Sisältää myös kartakkeen A map of Spitzbergen or Greenland, Iceland, and some part of Groenland &c.